Evaluation of serum lactate dehydrogenase and gamma glutamyl transferase in preeclamptic pregnancy and its comparison with normal pregnancy in third trimester - Sarkar, Purnima Dey; Sogani, Sonal (International Journal of Research in Medical Sciences, 2017)
Background: Preeclampsia affects about 5-8% of all pregnancies and is a major cause of maternal, fetal and neonatal mortality and morbidity. Evidences prove that endothelial cell and altered endothelial cell function play an important role in the pathogenesis of preeclampsia. Therefore serum lactate dehydrogenase (LDH) and serum gamma glutamyl transferase (GGT) are the useful biochemical markers reflecting the severity of the occurrence of preeclampsia. The objective was todetermine serum lactate dehydrogenase (LDH) and serum gamma glutamyl transferase (GGT) as biochemical markers in preeclamptic pregnant women and its comparison with normal pregnant women in third trimester. Methods: This is the case-control hospital based study carried in the Department of Biochemistry M.G.M. Medical College and associated M.Y. Hospital. Indore (M.P.). Normal pregnant women (n=48), women with preeclampsia (n=53) were included in the study. Both the groups were in their third trimester and of same age and same gestational age. Preeclamptic group was further divided into two subgroups mild (n=36) and severe (n=17) preeclampsia. Results: There were no significant differences among the three groups in age and body mass index but significantly higher differences in gestational age, systolic and diastolic blood pressure was observed. Higher values of serum lactate dehydrogenase (LDH) were found in mild and severe preeclamptic women than those of normal pregnant women in third trimester but the values of serum LDH was significantly elevated in severe preeclamptic women when comparison was done between mild and severe preeclamptic women. Serum GGT was significantly higher among all the groups. Conclusion: Elevated levels of serum LDH and serum GGT indicates the tissue damage related to endothelial vascular damage and are the main cause of the occurrence of preeclampsia.